Effectiveness of Genetic Parameter Estimation in a Small Flock of Merino Sheep with Shallow Pedigree - Serdar Duru; Mehmet Koyuncu (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the genetic and non-genetic parameters were estimated for growth traits of Karacabey merino sheep. Growth performance data refer to 1863 lambs born between 2016 and 2018. Analyses were carried out by restricted maximum likelihood fitting animal models and disregarding or including maternal genetic or maternal permanent environmental effect. Six different animal model were fitted for all traits, and the most suitable model for each trait was chosen after Akaike information criterion test (AIC). Year of birth, age of dam, type of birth and lamb sex were significant sources of variation on birth weight (BW), average daily gain (ADG), Kleiber ratio (KR), weaning weight (WW) and six month weight (6MW). Direct heritability (h^2) for BW, ADG and 6MW were 0.12, 0.02 and 0.04, respectively, however, for KR and WW were 0.00 model 6 (which the best). The estimates of maternal heritability (m^2) for ADG, KR and WW were 0.12, 0.04 and 0.04, respectively in model 5, also maternal heritability were low for BW and 6MW. Maternal permanent environmental effects (c^2) have high contribution to the explanation growth traits and were estimated between 0.19 and 0.75 for these traits. These results showed that selecting for improved maternal and/or direct effects for Karacabey merino in the herd would generate very slow genetic improvement in growth traits.